Respuesta :

Answer: Second Choice. √65

Step-by-step explanation:

Given information

a = 4

b = side (unknown)

c = 9

Given expression

b² = c² - a²

Substitute values into the expression

b² = (9)² - (4)²

SImplify by exponents

b² = 81 - 16

b² = 65

Square root both sides

√(b²) = √65

b = √65

Hope this helps!! :)

Please let me know if you have any questions

Answer:

√65

Step-by-step explanation:

    Since this is a right triangle, we can use Pythagorean Theorem to solve for the missing side.

Pythagorean Theorem: [tex]a^2+b^2=c^2[/tex]

  • a = leg
  • b = leg
  • c = hypotenuse

    In this instance, we are given a leg and the hypotenuse. Substitute the values into the theorem and solve for the missing side.

[tex]4^2+b^2=9^2\\\\16=b^2=81\\\\b^2=65\\\\b=\sqrt{65}[/tex]

Therefore, the value for the missing side is √65.